A colorimetric and ratiometric fluorescent probe for detection of palladium in the red light region1. Issue 65 (16th July 2015) - Xiang, Kaiqiang; Liu, Yunchang; Li, Changjiang; Tian, Baozhu; Zhang, Jinlong
<x xml:space="preserve">Abstract</x> We synthesized a colorimetric and ratiometric red-light emissive chemosensor with high selectivity and sensitivity towards palladium species.